Ascorbic acid supplementation has a cytoprotective effect on secondary biliary cirrhosis: experimental study in young rats - Matos Silva Passoni, Cynthia R. [UNESP]; Rabello Coelho, Claudio Antonio [UNESP] (Sociedade Brasileira de Pediatria, 2008)
Objective: To test whether ascorbic acid supplementation has any cytoprotective effect on a model of secondary biliary cirrhosis in young rats.Methods: We studied 40 Wistar rats weaned at the 21st postnatal day. Each group of 10 was subjected to one of the following four treatments, until 49th postnatal day, when they suffered euthanasia: 1) LC-double ligature and resection of the common bile duct and daily administration of ascorbic acid [100 mg/g of body weight (bw)]; 2) LA-double ligature and resection of the common bile duct and daily administration of aqueous vehicle (1 mL/g bw); 3) SC-sham operation and daily administration of ascorbic acid (100 mg/g bw); 4) SA-double ligature and resection of the common bile duct and daily administration of aqueous vehicle (1 mL/g bw). The rats were weighed daily. on the 27th day after the operation they received an intra-peritoneal injection of 1.5 mg/g bw of sodium pentobarbital, and the pentobarbital sleeping time was measured. Blood was collected for serum alanine aminotransferase and aspartate aminotransferase activity measurements, serum albumin and globulin concentrations, and the liver was assessed for liver water and fat content. Data were submitted to two-way ANOVA and paired comparisons between groups were tested using the SNK method. Significance level was set at 0.05.Results: Ascorbic acid supplementation attenuated the effects of cholestasis: decreased the pentobarbital sleeping time, serum globulin, and the liver fat content.Conclusions: Our results corroborate the hypothesis that ascorbic acid supplementation has a cytoprotective effect in secondary biliary cirrhosis.